Clustering and molecular states in neutron rich nuclei - Gnoffo, B.; Pirrone, S.; Politi, G.; Cardella, G.; De Filippo, E.; Geraci, E.; Maiolino, C.; Martorana, N. S.; Pagano, A.; Pagano, E. V.; Papa, M.; Risitano, F.; et al. (Frontiers in Physics, 2022)
An investigation plan of different clustering and molecular states in neutron rich isotopes of Lithium, Beryllium, Boron and Carbon, in the context of an experimental campaign at INFN-Laboratori Nazionali del Sud, is presented. High statistics and new information on known states and study on new states will be possible thanks to the high intensities available for the exotic beams, delivered by the FRAISE facility and thanks to the opportunity of using very performing experimental apparatus, as well as the detectors CHIMERA, FARCOS and NArCOS. Among these, the new hodoscope NArCOS, by detecting with high efficiency neutrons and providing high energy and angular resolutions, will allow also a precise study of reaction channels characterized by neutron emission.